2022
DOI: 10.1111/apa.16343
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension in children with obesity

Abstract: Aim:Obesity is an under-recognised risk factor for raised intracranial pressure in the paediatric population. The pathophysiology remains unclear. The aim of our study was to investigate the association between idiopathic intracranial hypertension (IIH) and weight in children. Methods:Patients diagnosed with IIH at a tertiary children's hospital were retrospectively identified between April 2017 and April 2019. Information regarding the patients' body mass index, presentation, investigation and treatment was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…During vaginal delivery, heavier birth weight may prolong labor and increase the risk of asphyxia and infection of the baby [27]. In addition, Balcer et al found that obesity in children correlated with an increased risk of primary ICH [28].…”
Section: Discussionmentioning
confidence: 99%
“…During vaginal delivery, heavier birth weight may prolong labor and increase the risk of asphyxia and infection of the baby [27]. In addition, Balcer et al found that obesity in children correlated with an increased risk of primary ICH [28].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity led to the emergence of multiple serious obesity-related comorbidities [ 2 ], and holds the potential to adversely impact virtually every system within the human body [ 3 , 4 ]. Children with obesity are at an increased risk of hyperinsulinemia [ 5 ], musculoskeletal problems [ 6 ] idiopathic intracranial hypertension [ 7 , 8 ] and other disease. Thus, obesity has escalated into one of the pressing public health crises of the current era.…”
Section: Introductionmentioning
confidence: 99%